c‐Met activation in lung adenocarcinoma tissues: An immunohistochemical analysis - Yu Nakamura; Toshiro Niki; Akiteru Goto; Teppei Morikawa; Keiji Miyazawa; Jun Nakajima; Masashi Fukayama (2007)
c‐Met is often overexpressed in non‐small cell lung cancer, but it remains unsolved whether its overexpression leads to its activation. We used an antibody specific to phospho‐c‐Met (Tyr1235) to investigate c‐Met activation immunohistochemically in 130 surgically resected lung adenocarcinomas. The expression of c‐Met and hepatocyte growth factor (HGF) was also investigated. Phospho‐c‐Met was positive in 21.5% (28/130) of cases. c‐Met was positive in 74.6% of cases (97/130) and was expressed at high levels in 36.1% of cases (47/130). HGF was expressed at high levels in 31.5% of cases (41/130). Phospho‐c‐Met was correlated with high levels of HGF ( P = 0.0010) and high levels c‐Met expression ( P = 0.0303), but it was also found to be positive in 12 cases with little to no HGF expression. Phospho‐c‐Met expression was significantly associated with tumor differentiation ( P = 0.0023) and papillary histology ( P = 0.0011), but not with pathological stage, lymph node metastasis or survival. High levels of c‐Met and HGF were also associated with papillary histology ( P = 0.0056 and P = 0.0396, respectively), but not with tumor differentiation. Phospho‐c‐Met was correlated with phospho‐Akt ( P = 0.0381), but not with phospho‐Erk or phospho‐Stat3. Phospho‐Akt expression was marginally correlated with the expression of phospho‐epidermal growth factor receptor (EGFR) ( P = 0.0533) and, importantly, it was strongly correlated with the expression of either phospho‐c‐Met or phospho‐EGFR ( P = 0.0013). The data suggest that in lung adenocarcinoma tissue, c‐Met activation may take place either ligand‐dependently or ligand‐independently via c‐Met overexpression. c‐Met activation may play special roles in the papillary subtype and in well differentiated lung adenocarcinomas. ( Cancer Sci 2007; 98: 1006–1013)